Cytokine‐induced transient monocyte IL‐7Ra expression and the serum milieu in tuberculosis. Issue 6 (25th March 2022) - Harelimana, Jean De Dieu; Ahor, Hubert Senanu; Benner, Bastian; Hellmuth, Sabine; Adankwah, Ernest; Minadzi, Difery; Aniagyei, Wilfred; Lamptey, Millicent Naa Koshie; Arthur, Joseph; Yeboah, Augustine; Abass, Mohammed K.; Debrah, Linda Batsa; et al.
Abstract: Bacterial components and cytokines induce IL‐7 receptor (IL‐7Rα) expression in monocytes. Aberrant low IL‐7Rα expression of monocytes has been identified as a feature of tuberculosis immunopathology. Here, we investigated the mechanisms underlying IL‐7Rα regulation of monocytes and tuberculosis serum effects on IL‐7Rα expression. Serum samples from tuberculosis patients and healthy controls, cytokine candidates, and mycobacterial components were analyzed for in vitro effects on IL‐7Rα expression of primary monocytes, monocyte‐derived macrophages (MDM), and monocyte cell lines. IL‐7Rα regulation during culture and the role of FoxO1 were characterized. In vitro activation‐induced IL‐7Rα expression in human monocytes and serum samples from tuberculosis patients boosted IL‐7Rα expression. Although pathognomonic tuberculosis cytokines were not associated with serum effects, we identified cytokines (i.e., GM‐CSF, IL‐1β, TNF‐α, IFN‐γ) that induced IL‐7Rα expression in monocytes and/or MDM comparable to mycobacterial components. Blocking of cytokine subsets (i.e., IL‐1β/TNF‐α in monocytes, GM‐CSF in MDM) largely diminished IL‐7Rα expression induced by mycobacterial components. Finally, we showed that in vitro‐induced IL‐7Rα expression was transient and dependent on constitutive FoxO1 expression in primary monocytes and monocyte cell lines. This study demonstrated the crucial roles of cytokines and constitutive FoxO1 expression for transient IL‐7Rα expression in monocytes. Abstract : Mycobacterium tuberculosis cell wall proteins (CW Mtb ) and the Toll‐like receptor 2 agonist (Pam3Cysk4, PAM3) induce IL‐7Rα expression indirectly via different autologous cytokines (i.e., IL‐1ß/TNF‐α in monocytes, GM‐CSF in monocyte‐derived macrophages [MDM]). IL‐7Rα expression on monocytes is transiently induced by cytokines and involves constitutive expression of transcription factor FoxO1. These findings may explain promoting tuberculosis (TB) serum milieu on monocyte IL‐7Rα expression.